Analisis Bibliometrik Penelitian Pinjaman Online: Tren, Tema, dan Kontribusi Ilmiah Dari 2019 Hingga 2023 - Fitrianti, Dwi; Wahyuni, Titin; Amelia, Azarine Nahdah; Octavia, Winda Dwi; Riyadi, Slamet; Pandin, Maria Yovita R. (IAI Nasional Laa Roiba Bogor, 2024)
The aim of this study is to analyze the research topics of online lending along with the trends, themes and contributions used. The output of this study is to find other topics that can be used as research variables in the future. The research method used is a literature review using bibliometric analysis extraction through the Publish or Perish application with the Google Scholar database. After narrowing down the research results to journal articles specifically on online lending, 122 articles were obtained from 200 initial search results.The research results were then compiled through the Mendeley application and visualized through the VOSviewer application to see research trends.The results showed that the classification of online lending topics was divided into four clusters centered on fintech lending, p2p lending, consumer protection and pandemic. This research is limited by the lack of diversity in the research topics examined and the software used.